2017
DOI: 10.3748/wjg.v23.i28.5041
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer in young adults: A difficult challenge

Abstract: Sporadic colorectal cancer (CRC) is traditionally diagnosed after the sixth decade of life, and current recommendations for surveillance include only patients older than 50 years of age. However, an increasing incidence of CRC in patients less than 40 years of age has been reported. This occurrence has been attributed to different molecular features and low suspicion of CRC in young symptomatic individuals. When confronting young-onset CRC with older patients, issues such as biological aggressiveness, stage at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
77
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 31 publications
5
77
0
2
Order By: Relevance
“…However, LSs represent 9.2% –21.3% of cases in this subgroup14–21 and this research like other current studies55–57 revealed it is a heterogeneous disease, which includes cases with a high familial component other than LS as well as a substantial proportion of sporadic cases with distal location.…”
Section: Discussionsupporting
confidence: 81%
“…However, LSs represent 9.2% –21.3% of cases in this subgroup14–21 and this research like other current studies55–57 revealed it is a heterogeneous disease, which includes cases with a high familial component other than LS as well as a substantial proportion of sporadic cases with distal location.…”
Section: Discussionsupporting
confidence: 81%
“…The distribution of incidence by age is important because it guides the screening strategy and particularly the lower limit of age to be targeted by this intervention. Indeed, it is clear that for ages with low specific incidence rates (young adult) with generally poor prognosis and sometimes familial or genetic characteristics are not suitable for mass screening (the cost-effectiveness of screening would be reduced) [13,[56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer is the third most commonly diagnosed malignancy and the fourth leading cause of tumor-related death all over the world, accounting for ∼1.4 million newly diagnosed cases and almost 0.7 million deaths annually (1)(2)(3). Although colorectal cancer incidence and mortality rates have been stabilizing or declining in a number of high human development index countries, the rapid increases in incidence and mortality of colorectal cancer are observed in medium or low income countries (4) and in patients <40 years old (5,6). Moreover, most cases of colorectal cancer develop slowly over several years through adenocarcinoma sequence despite strong hereditary components (7).…”
Section: Introductionmentioning
confidence: 99%